2015
DOI: 10.1155/2015/182837
|View full text |Cite
|
Sign up to set email alerts
|

Microcurrent Stimulation at Shenmen Acupoint Facilitates EEG Associated with Sleepiness and Positive Mood: A Randomized Controlled Electrophysiological Study

Abstract: To examine the electrophysiological effects of microcurrent stimulation at the Shenmen acupoint, 40 healthy normal subjects were randomly assigned to a placebo group (sham stimulation) and an experimental group (bilateral electrocutaneous stimulation at the Shenmen). The following two electroencephalographic indicators were used to measure brain activity. (1) Arousal level was measured with reference to log-transformed absolute alpha power and power source and analyzed using low-resolution electromagnetic tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 111 publications
2
11
1
Order By: Relevance
“…Previous research demonstrated that MS at the Shenmen acupoint (HT7) changed brain activity as measured with EEG, indicating decreased sleepiness and increased positive mood in healthy volunteers ( Cheung et al, 2015 ). The present study’s findings partially align with Cheung et al (2015) , as participants felt more well-rested and less exhausted by the exercise after MS. Something similar was recently demonstrated by Piras et al (2021) who showed speeded physical recovery when RT was followed by MS ( Piras et al, 2021 ). However, unlike Cheung et al (2015) , no effects of MS on positive mood or mood in general were found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research demonstrated that MS at the Shenmen acupoint (HT7) changed brain activity as measured with EEG, indicating decreased sleepiness and increased positive mood in healthy volunteers ( Cheung et al, 2015 ). The present study’s findings partially align with Cheung et al (2015) , as participants felt more well-rested and less exhausted by the exercise after MS. Something similar was recently demonstrated by Piras et al (2021) who showed speeded physical recovery when RT was followed by MS ( Piras et al, 2021 ). However, unlike Cheung et al (2015) , no effects of MS on positive mood or mood in general were found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides physical advantages, MS has beneficial effects on psychological parameters, like mood and arousal levels. For example, Cheung et al (2015) demonstrated that MS at the Shenmen acupoint (HT7), located at the wrist crease of the radial side of the flexor carpi ulnaris tendon, led to a change in brain waves as determined with EEG compared with sham treatment. These activation patterns were previously related to mood-enhancement and decreased arousal levels or higher sleepiness; therefore, findings suggest that MS can affect these psychological processes ( Cheung et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study [48] indicates that auricular acupressure may improve sleep quality by increasing heart rate variability, as well as lowering blood pressure and heart rate. One study [49] reported that microcurrent stimulation at Shenmen acupoint could promote EEG changes related to sleepiness and positive mood. Another study [50] found that acupuncture can significantly increase endogenous melatonin secretion at night, which may be one of the mechanisms for improving sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…HT-7 has been frequently used for treating neuropsychological impairments such as insomnia, amnesia, dementia, and anxiety neurosis [ 36 – 39 ]. Research studies [ 40 ] indicate that stimulating HT-7 has significant effects on brain activity. Thus, animal experiments are essential to investigate the molecular mechanism of LA at HT-7 on brain function.…”
Section: La On Single Pointmentioning
confidence: 99%